Baliuta, K. A. (2022). Traveling back in time through text (on Ge Fei’s “Jinse”) - К. A. Baliuta (Шаги)
The article is devoted to the linguistic and compositional analysis of “Jinse” (Brocade Zither, 1993), a short story by Ge Fei, a modern Chinese avant-garde prose writer (born in 1964). In the story, the main character, Feng Zicun, finds himself in various time periods of Chinese history, switching roles from a mysteriously imprisoned hermit to a medieval literatus to a tea merchant and, finally, to an ancient state ruler in the time of Western Chu (206–202 BC). The main features of the story include a complex narrative structure represented by episodes tied together in a system of “dream in a dream”, each episode going farther back in time, as well as a complex language style. The text of the story starts with the modern Chinese language and by the end gradually shows more and more similarities to the classical Chinese language wenyan with its classical syntax structure, conjunctions, one-syllable lexis, parallelism, rhythm, etc. The text of the story actually acts as a “time-machine” that invites the reader to travel back in time. Such features make Ge Fei’s prose very challenging for a researcher and a translator. The article also addresses the concept of time in Ge Fei’s fiction and a significant number of allusions in his writings (as the story title is an allusion to Li Shangyin’s poem).